ANALISA PENGARUH WAKTU DAN SUHU PADA RUANG BAKAR INCINERATOR MENGGUNAKAN ASTM A36 TERHADAP NILAI KOROSI - Nugroho, Eko; Rajabiah, Nurlaila; Pramudya, Yudha (TURBO [Tulisan Riset Berbasis Online], 2024)
Incinerator is a device designed and used for burning non-metal solid waste using certain technology at high temperatures. Corrosion is damage or destruction of materials due to chemical reactions in the surrounding environment. High temperature and usage time in incinerators made from ASTM A36 is one of the factors for corrosion. The purpose of the research is to determine the effect of combustion time on corrosion value and the effect of high temperature combustion temperature on corrosion value. The research method carried out is an experimental approach by putting the ASTM A36 steel plate into the oven with the temperature to be used, namely 600 0C, 650 0C, and 700 0C with the heating time to be used for 3 hours, 5 hours, and 7 hours. The corrosion process is carried out by leaving it in the open air for 7 days and after that data collection and calculation of corrosion values are carried out. From the calculation results at a temperature of 600 0C and a heating time of 3 hours, the lowest corrosion value is 0.42020 mm/year and the highest occurs at a temperature of 700 OC and a heating time of 7 hours of 1.77629 mm/year.